Essentials of human anatomy and physiology - Marieb, Elaine N. (California : Addison-Wesley, 1997)
An excellent introduction to the structure and function of the human body, Marieb's classic uses an easy-to-read writing style that provides accurate and thorough coverage, while making concepts easy to understand.
The human body -- Basic chemistry -- Cells and tissues -- Skin and body membranes -- The skeletal system -- The muscular system -- The nervous system -- Special senses -- The endocrine system -- Blood -- The cardiovascular system -- The lymphatic system and body defenses -- The respiratory system -- The digestive system and body metabolism -- The urinary system -- The reproductive system -- Appendixes.
Includes index.
Keywords: HUMAN PHYSIOLOGY; HUMAN ANATOMY